2017
DOI: 10.3389/fneur.2017.00071
|View full text |Cite
|
Sign up to set email alerts
|

A Postural Tremor Highly Responsive to Transcranial Cerebello-Cerebral DCS in ARCA3

Abstract: Background and objectivesCerebellar ataxias are disabling disorders that impact the quality of life of patients. In many cases, an effective treatment is missing. Despite the increasing knowledge on the pathogenesis of cerebellar disorders including genetic aspects, there is currently a gap in the therapeutical management of cerebellar deficits. Cerebellar ataxia associated with ANO10 mutation (ARCA3) presents a disabling cerebellar syndrome. The aim of this study is to report a patient with a marked postural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Figure 2c shows the different TMS protocols commonly applied [10,25,26]. Cerebellar tDCS might be beneficial for patients with cerebellar neurodegenerative diseases such as ataxia (e.g., spinocerebellar ataxias (SCAs)) [27][28][29] and tremor (e.g., essential tremor (ET)) [30][31][32], but only a few studies have assessed the role of cerebellar stimulation during rehabilitation after cerebellar stroke [e.g., [31][32][33][34]. Despite the substantial differences in the stimulation protocol (four studies; Calzolari et al [33]: excitatory anodal tDCS over the lesioned hemisphere; Torriero et al [34]: inhibitory 1 Hz rTMS over the unlesioned hemisphere; Kim et al [35]: inhibitory 1 Hz rTMS over the lesioned hemisphere; and Bonnì et al [36]: excitatory iTBS over the lesioned hemisphere), all studies found have marked improvements after cerebellar stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2c shows the different TMS protocols commonly applied [10,25,26]. Cerebellar tDCS might be beneficial for patients with cerebellar neurodegenerative diseases such as ataxia (e.g., spinocerebellar ataxias (SCAs)) [27][28][29] and tremor (e.g., essential tremor (ET)) [30][31][32], but only a few studies have assessed the role of cerebellar stimulation during rehabilitation after cerebellar stroke [e.g., [31][32][33][34]. Despite the substantial differences in the stimulation protocol (four studies; Calzolari et al [33]: excitatory anodal tDCS over the lesioned hemisphere; Torriero et al [34]: inhibitory 1 Hz rTMS over the unlesioned hemisphere; Kim et al [35]: inhibitory 1 Hz rTMS over the lesioned hemisphere; and Bonnì et al [36]: excitatory iTBS over the lesioned hemisphere), all studies found have marked improvements after cerebellar stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a similar trial with 2 weeks of anodal ctDCS in patients with spinocerebellar ataxia type 3 are awaited (Maas et al, 2019). An improvement of marked postural tremor in cerebellar ataxia associated with ANO10 mutation was noted with cerebello-cerebral stimulation (anode over cerebellum and cathode over M1, 1.5 Ma, 20 min) (Bodranghien et al, 2017). No significant beneficial effect was noted with anodal tDCS to the cerebellum or the motor cortex in grip force control (2 mA, 25 min) (John et al, 2017) or forcefield reaching adaptation (2 mA, 22 min) (Hulst et al, 2017) in patients with cerebellar ataxia.…”
Section: Cerebellar Ataxiamentioning
confidence: 98%
“…Cervical dystonia (McCambridge and Bradnam, 2018;Summers et al, 2018) 8. Cerebellar ataxia (Grimaldi and Manto, 2013;Grimaldi et al, 2014b;Benussi et al, 2015Benussi et al, , 2017bBenussi et al, , 2018Bodranghien et al, 2017;Hulst et al, 2017;John et al, 2017;Maas et al, 2019;Pilloni et al, 2019;Vavla et al, 2019) 9. Essential tremor (Gironell et al, 2014;Helvaci et al, 2016) 10.…”
Section: Mode Of Tesmentioning
confidence: 99%
“…Bodranghien and colleagues (2017) [24] conducted a single case study in a patient with ANO10 mutation (ARCA3). They delivered anodal tCCDCS over the cerebellum with a return electrode on the contralateral motor cortex.…”
Section: Introductionmentioning
confidence: 99%